(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
The paper outlines the political, patrimonial and economic relations linking in the 9th and 10th centuries Ravenna - and the powers that were based there – to the territory of Comacchio, characterised by a peculiar evironment and by the presence of specific resources. Particular attention will be paid to the expansion of the influence of the Ravenna archbishops towards the Po delta, to the origins of the monastery of Santa Maria di Pomposa, and to the extensive presence of landed estates of fiscal origin. The numerous disputes that arose from the Ottonian age onwards around these lands and resources will also be contextualised in the attempt to reassert royal control over a vast set of assets that seem to have mantained a public feature over time